Stabilization of Electrical Parameters of Machine-Converter Voltage Source - Dementyev, Yu. N.; Glazachev, A. V.; Negodin, K. N.; Vajda, I.; Susdorf, V. I. (EAI Endorsed Transactions on Energy Web, 2018)
The paper is devoted to development of Machine-Converter Source (MCS), which forms the output voltage waveform of electric generator as sum of EMFs with near frequencies. As electric modulation generator is used a synchronous generator and asynchronous exciter that have both common driving shaft and common housing. We studied the automatic control systems for output electrical parameters of MCS when changing speed of driving shaft and load power in wide ranges.